ACUTE TOXICITY TEST OF RED ONION (Allium Cepa L) SKIN EXTRACT ON KIDNEY HISTOPATHOLOGY OF RATS (Rattus Norvegicus) - Brahmantya Putra, Denny Christian; Helianti, Dina; Wahyudi, Septa Surya; Dewi, Rosita (Indonesian Urological Association, 2026)
Introduction: Shallots (Allium cepa L.) are known to contain quercetin, which is helpful as an antioxidant, but its accumulation in the body can be toxic. Objective: This study aims to determine the effect of administering red onion skin extract on histopathology and weight of the kidney, body weight, and clinical symptoms, as well as determining the LD50. Material & Methods: This research was conducted according to OECD guideline No. 420 Fixed Dose Procedures. Rats were allocated to a control group that was given 3% DMSO and a treatment group that was given red onion peel extract at a dose of 5000 mg/kgBW. Kidney histopathology slides with Hematoxylin-eosin staining were observed by two observers in five fields of view using Fiji ImageJ software and assessed based on the Kocoglu scoring. Kidney histopathology data was analyzed using the Mann-Whitney test, while kidney weight and body weight gain used the Independent Sample T-test. Results: The treatment group experienced significantly higher body weight gain than the control group. On the other hand, observations of the histopathological appearance and weight of the kidney did not show any significant differences. Observation of clinical symptoms showed normal results with no deaths. Conclusion: Administration of 5000 mg/kgBW red onion skin extract in the acute toxicity test had no effect on the histopathology and weight of kidney rats, but had a significant effect on body weight gain. The LD50 of red onion skin extract was found to be >5000 mg/kgBW. Keywords: Red onion skin extract, acute toxicity test, LD50, kidney histopathology.